Characterizing mold VOCs in residential structures impacted by flood - Murphy, Molly, author; Schaeffer, Joshua, advisor; Magzamen, Sheryl, committee member; Carter, Ellison, committee member (Colorado State University. Libraries, 2024)
Mold growth is a health concern for people re-entering their homes after a flooding event. Mold exposure can be hazardous, especially for people with asthma. Mold produces volatile organic compounds (VOCs) as it grows, and those VOCs can be used to detect the presence of mold. While VOC profiles of mold have been constructed in laboratory settings, there has been little work with samples directly from the field. VOC samples were taken from the homes of 55 Houston residents. 33 homes had been flooded, and 22 had not. The VOCs were analyzed using GCMS and identified using a NIST library of mass spectra. The VOCs found in flooded homes were compared to VOCs found in unflooded homes. There was a difference in VOCs identified, and the concentration of those VOCs, in flooded versus non-flooded homes, and some of those VOCs have been previously associated with mold growth. However, the origin of those VOCs is still not clear. Further work should include associating the VOCs found with the maximum water levels in the flooded homes, and with health data collected from the participants.
Keywords: indoor air quality; mold; floods; mold VOC; microbial VOC